1993
DOI: 10.1111/j.1460-2695.1993.tb00112.x
|View full text |Cite
|
Sign up to set email alerts
|

Notch Root Crack Closure Under Cyclic Inelasticity

Abstract: Aluminium alloy sheet coupons with a central hole were tested in fatigue under specially designed programmed load sequences. Electron microscopy of the fatigue fracture surfaces showed striation mode fatigue crack extension up to more than a millimeter before onset of rapid failure. Crack opening stress was determined from striation patterns. Under variable amplitude loading and conditions of notch root cyclic inelasticity, crack opening stress exhibits noticeable hysteresis. The hysteresis is attributed to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

1993
1993
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 10 publications
1
17
0
2
Order By: Relevance
“…The associated mixed-mode nature of crack-tip loading may have induced damage due to rubbing on the S cl segment. The same conclusion may be drawn from other typical fractographs that appear as in Earlier work on hysteretic behaviour in crack closure had indicated that hysteresis diminishes with increase in crack size [6,17]. The 15 per cent difference between S cl and S op , as seen from Fig.…”
Section: Sem Observations and Correlation With Load Sequencesupporting
confidence: 80%
“…The associated mixed-mode nature of crack-tip loading may have induced damage due to rubbing on the S cl segment. The same conclusion may be drawn from other typical fractographs that appear as in Earlier work on hysteretic behaviour in crack closure had indicated that hysteresis diminishes with increase in crack size [6,17]. The 15 per cent difference between S cl and S op , as seen from Fig.…”
Section: Sem Observations and Correlation With Load Sequencesupporting
confidence: 80%
“…This &-level decreases with increasing S,. A slight deviation between cop and as described by Sunder [16], was observed only in few cases for small surface cracks in combination with high load amplitude. A similar crack opening behaviour was determined for the specimens of A15086.…”
Section: Crack Opening and Closure Strainsmentioning
confidence: 76%
“…Summarizing the statements made above it can be speculated whether the method of detecting crack opening levels which is-in principle-a valuable tool really provides the accuracy the authors claim [1,2]. It will be interesting to discuss further results which might be stimulated by the examination presented above.…”
Section: Evaluation Of Striation Spacingsmentioning
confidence: 92%